Role of Talent Management and Culture in Performance at Perum Perhutani - Hermanto, Hermanto; Hudzafidah, Hudzafidah; Marifah, Muliatul (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
Enhancing the effectiveness of employees within an organization to achieve both quality and quantity in goal attainment is a primary objective. This pursuit considers a thorough evaluation of assessments and respects the organizational cultural values. This research aims to explore the impact of Talent Management, Organizational Culture, and Competence as moderating factors on employee performance within Perum Perhutani City "PB". A comprehensive sample of 74 respondents was thoughtfully selected for this study. The research employed a quantitative approach, utilizing the SmartPLS 4 tool for data analysis through Partial Least Square (PLS) analysis. The findings from this study underscore a significant correlation between organizational culture and employee performance. However, it's noteworthy that the research did not identify a substantial impact of talent management on employee performance. In terms of employee competence, it's evident that it exerts a considerable influence on employee performance. Nevertheless, it's important to mention that employee competence does not exhibit a moderating effect on the relationship between talent management, organizational culture, and employee performance at Perum Perhutani City "PB". In other words, competence is not a variable that strengthens or weakens the influence of talent management and organizational culture on employee performance